Organic cocrystals : beyond electrical conductivities and field-effect transistors (FETs) - Huang, Yinjuan (2021)
Organic cocrystals based on noncovalent intermolecular interactions (weak interactions) have aroused interest owing to their unpredicted and versatile chemicophysical properties and their applications. In this Minireview, we highlight recent research on organic cocrystals on reducing the aggregation-caused quenching (ACQ) effect, tuning light emission, ferroelectricity and multiferroics, optical waveguides, and stimuli-responsiveness. We also summarize the progress made in this field including revealing the structure-property relationships and developing unusual properties. Moreover, we provide a discussion on current achievements, limitations and perspectives as well as some directions and inspiration for further investigation on organic cocrystals.